Spectroscopic Study of the Influence of Corona Discharge Polarity on Air Discharge Characteristics in Liquid Electrodes System - Ahmed , Lubna Salah; Abbas, Qusay Adnan (Iraqi Journal of Science, 2026)
In this work, the influence of positive and negative corona discharges on the variation of air gap discharge characteristics with applied voltage under atmospheric pressure in the tap water electrodes system has been investigated. The discharge characteristics included emission spectra, electron temperature, electron number density, Debye length and plasma frequency. The results show no effect of polarity of space charge on the emission peaks. While the intensity of emission peaks increases when the presence of the negative space charge forms the negative corona discharge. Increasing the applied voltage increases the (Te , ne , ) plasma parameters while parameters (λD , ND) decrease. The types of corona discharge do not affect the behavior of plasma parameters with the increased applied voltage, but it changes in value either rising or falling. The behavior of the discharge characteristics at the applied voltage range 0-25 kV showed different behavior when the applied voltage was greater than 25 kV in both types of corona discharge with a greater rate when the positive corona discharge was established.